The Development of Interactive E-Module Using Flipbookmaker for English Structure Learning at an Indonesian University - Afrianto Daud; Supriusman Supriusman; Rozalinda Rozalinda; Zaldi Harfal; Ade Suryani; Ovia Nabilla; Zahrah Thahirah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aims to develop an interactive e-module for English Structure course to support digital learning in the English Study Program, Universitas Riau, Indonesia. The research used a Research and Development (R&D) approach and applied the ADDIE model consisting of five stages; analyse, design, development, implement and evaluate. The products developed were animated videos and interactive quizzes integrated into an electronic module using the Flipbook maker application. The e-module consists of three chapters with several sections in each chapter: video based explanation, text based description, example, interactive quizzes, and chapter summary. The results of the validations of media expert and material expert of the animated videos are 3.55 (very valid) while the interactive quizzes got an average score of 3.85 (very valid). Then, for the validations of the e-module, it go an average score of 3.96 (very valid) and 3.23 (valid) from the material expert and the media expert, respectively. On the whole, the average score of the validations is 3.60 (very valid). The e-module has been implemented to a group of students (n=20). The students’ responses show that the e-module has a very good category (3.75 for the attractiveness aspect and 3.61 for the convenience aspect). Therefore, it can be concluded that the e-module has a very good quality, both in terms of its materials and media, and is eligible to be utilized as a digital learning resource for Pre-Intermediate Structure course in the English department of Universitas Riau, Indonesia.